The initial conditions at release in hammer throw of world class top athletes - Okamoto, A.; Sakurai, S.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: In hammer throw, the influence of the air resistance is negligibly smaller in comparison with javelin and discus throw. Therefore, the throwing distance of a projectile object is practically determined by the initial conditions at release such as initial velocity, the angle of projection and the release height. The purpose of this study was to investigate the influence of initial conditions at release on the throwing distance of hammer throw.